Legal Certainty in First-Time Land Registration Based on a Juridically Defective Compensation Certificate (SKGR): An Analysis of Decision Number 58/G/2024/PTUN.PBR, Decision Number 81/B/2025/PT.TUN.MDN, and Decision Number 799 K/TUN/2025 - Luthvia Nur Azizah; Siti Hajariah A; Omar Damaraji Dewananda (Jurnal Smart Hukum (JSH), 2026)
This study aims to analyze the legal certainty of first-time land registration based on a juridically defective Compensation Certificate (Surat Keterangan Ganti Rugi/SKGR) and the legal consequences of issuing a Certificate of Ownership resulting from such registration, as examined in Decision Number 58/G/2024/PTUN.PBR in conjunction with Decision Number 81/B/2025/PT.TUN.MDN and Decision Number 799 K/TUN/2025. This research employs a normative legal research method using statutory and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively through a prescriptive method. The findings indicate that first-time land registration based on an SKGR that has lost its juridical validity cannot provide complete legal certainty for rights holders. Courts at all levels found that the issuance of the certificates contained procedural and substantive defects due to the use of a revoked SKGR, inconsistencies between physical data and the underlying title, failure to conduct the mandatory public announcement, and disregard of the rights of the party who had previously possessed the land. Consequently, the certificates were declared null and void and were ordered to be revoked by the National Land Agency. The decisions affirm that legal certainty in land registration can only be achieved when all legal requirements and procedures are properly fulfilled.